THE IMPACT OF THE COVID-19 PANDEMIC ON EDUCATION - Dinda Dinda; Ririn Tjahyaningsih (Cakrawala Pedagogik, 2025)
The Covid-19 pandemic has brought significant changes in various aspects of life, particularly in the field of education. Government policies to limit face-to-face activities directly impacted the teaching and learning process in schools. This study aims to describe the impacts of the Covid-19 pandemic on education, both positive and negative. The method used is a literature review by analyzing various sources related to educational policies during the pandemic. The findings show that the pandemic created several challenges, including the decline in the quality of learning interactions, limited access to technology, and the digital divide among students. Furthermore, students’ psychological conditions were also affected due to limited social interactions. On the other hand, the pandemic accelerated digital transformation in education, improved teachers’ skills in using technology, and encouraged various online learning innovations. Thus, the Covid-19 pandemic not only posed obstacles but also provided opportunities to strengthen a more adaptive and flexible education system in the future